Guanosine inhibits hepatitis C virus replication and increases indel frequencies, associated with altered intracellular nucleotide pools. - Sabariegos, Rosario; Ortega-Prieto, Ana María; Diaz-Martínez, Luis; Grande-Pérez, Ana; García Crespo, Carlos; Gallego, Isabel; De Ávila, Ana Isabel; Albentosa-González, Laura; Soria, María Eugenia; Gastaminza, Pablo; Domingo, Esteban; Perales, Celia; et al. (PLOS, 2022)
In the course of experiments aimed at deciphering the inhibition mechanism of mycophenolic acid and ribavirin in hepatitis C virus (HCV) infection, we observed an inhibitory effect of the nucleoside guanosine (Gua). Here, we report that Gua, and not the other standard nucleosides, inhibits HCV replication in human hepatoma cells. Gua did not directly inhibit the in vitro polymerase activity of NS5B, but it modified the intracellular levels of nucleoside di- and tri-phosphates (NDPs and NTPs), leading to deficient HCV RNA replication and reduction of infectious progeny virus production. Changes in the concentrations of NTPs or NDPs modified NS5B RNA polymerase activity in vitro, in particular de novo RNA synthesis and template switching. Furthermore, the Gua-mediated changes were associated with a significant increase in the number of indels in viral RNA, which may account for the reduction of the specific infectivity of the viral progeny, suggesting the presence of defective genomes. Thus, a proper NTP:NDP balance appears to be critical to ensure HCV polymerase fidelity and minimal production of defective genomes.
Keywords: Virología; Virus de la hepatitis; Nucleósidos; Nucleótidos; Genómica; Acido ribonucleico - Síntesis; ARN - Síntesis; Virology; Hepatitis virus